2020
DOI: 10.1002/for.2736
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting volatility with outliers in Realized GARCH models

Abstract: The Realized generalized autoregressive conditional heteroskedasticity (GARCH) model proposed by Hansen is often applied to forecast volatility in high-frequency financial data. It is frequently found, however, that the distribution of the estimated residuals from Realized GARCH models has peak fat-tail characteristics. Considering this feature may be a result of neglected additive outliers (AOs) and innovative outliers (IOs), this paper proposes the Realized GARCH model with additive outlier and innovative ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This method can synthesize the information of multiple models, but it also needs to determine the appropriate model set, model weight, model selection criteria, etc. Cai [23] used dynamic model averaging method to establish a volatility prediction model based on dynamic quantile regression. Xiong Tao and Bao Yukun [24] also used dynamic model averaging method to predict soybean futures price, and found that this method can effectively improve the accuracy and robustness of soybean futures price prediction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This method can synthesize the information of multiple models, but it also needs to determine the appropriate model set, model weight, model selection criteria, etc. Cai [23] used dynamic model averaging method to establish a volatility prediction model based on dynamic quantile regression. Xiong Tao and Bao Yukun [24] also used dynamic model averaging method to predict soybean futures price, and found that this method can effectively improve the accuracy and robustness of soybean futures price prediction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Forecasting volatility under the assumption of normal distribution may lead to underestimation or overestimation of actual market volatility. Numerous studies have shown that asymmetric fat-tailed distribution can improve the forecasting effects of volatility (see, e.g., Tian & Hamori, 2015;Wu et al, 2020;Cai et al, 2021). Therefore, we also consider the asymmetric and fat-tailed characteristics of financial returns and introduce skewed-t distribution into the MF-MoP model to better describe the characteristics of volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the GARCH model is very general, there are serious challenges, especially when there are outliers. Previous studies have found that outliers can have detrimental effects on parameter estimate [10][11][12] , identification and estimation 13,14 and forecasting 13,15 . Therefore, robust methods are more preferred by researchers to reduce the influence of outliers.…”
Section: Introductionmentioning
confidence: 99%